Efforts to Prevent Violence in Dating - Karimah Darojat; Elok Halimatus Sa’diyah; Rifa Hidayah (Penerbit Hellow Pustaka, 2024)
Dating violence includes physical, emotional, verbal, social and sexual aggressive behavior aimed at controlling and hurting a parter. Dating violence is in second place in cases of violence against women. This makes it necessary to conduct studies regarding preventing cases of dating violence. The method used in this research is literature study, data was obtained from previous research articles which were then analyzed critically using the content analysis method. The aim of this research is to discuss efforts to prevent violence in dating. The results obtained are that prevention of dating violence can be done by victims and perpetrators. From the victim’s side, prevention can be done in the form of changing the meaning of love, then changing the belief from love is having to love is a process of becoming. Furthermore, by improving assertive attitudes, self-images, self-esteem and perceptions about gender which can be done by educational institutions and related agencies. Meanwhile, efforts to prevent violence in dating from the perpetrator’s side can be carried out by the family. Families can provide education about healthy relationships and provide direct examples.